High-barrier bamboo powder biodegradable composite packaging material and co-extrusion molding method thereof

CN122878726APending Publication Date: 2026-10-09SHANGHAI BLOPAK NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611135193.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,竹粉表面含有较多亲水性羟基,容易吸收水分,且竹粉与聚乳酸、生物降解聚酯等疏水性树脂之间的界面相容性较差,竹粉直接加入树脂后容易出现团聚、界面脱离及微孔缺陷,使水蒸气、氧气和气味分子沿竹粉与树脂之间的界面间隙快速渗透,导致所得包装材料难以同时兼顾较高竹粉添加量、机械强度和阻隔性能

Benefits of technology

该高阻隔竹粉生物降解复合包装材料及其共挤成型方法,通过对不同粒径的竹粉进行干燥、柠檬酸处理和植物蜡包覆,降低竹粉含水率并封闭其表面吸水通道,同时利用环氧大豆油和柠檬酸改善竹粉、热塑性淀粉与生物降解树脂之间的界面结合,减少材料内部的孔隙和界面裂纹;通过将纳米粘土与纳米纤维素预先制成片层—纤维复合阻隔粉体,使纳米纤维素连接并分隔纳米粘土片层,降低阻隔组分团聚程度;进一步采用表层—芯层—表层三层共挤结构,将复合阻隔粉体集中配置于两侧表层,将竹粉和热塑性淀粉集中配置于芯层,并通过共挤剪切、压延牵伸和热定型使纳米粘土片层及竹粉沿包装材料表面方向定向排列,从而在材料厚度方向形成多级弯曲渗透路径,在保持较高竹粉含量和生物降解性能的同时,提高包装材料的氧气阻隔性、水蒸气阻隔性、层间结合强度、尺寸稳定性及共挤加工稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878726A_ABST
    Figure CN122878726A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high barrier bamboo powder biodegradable composite packaging materials and its co-extrusion forming method, it is related to polyester degradable plastic technical field, the composite packaging material includes polylactic acid, biodegradable polyester, bamboo powder, thermoplastic starch, nano clay, nanocellulose, vegetable wax, epoxy soybean oil, citric acid, talcum powder, stearic acid and antioxidant.The application is dried, acidified and hydrophobic coated by bamboo powder, and nano clay and nanocellulose are made into composite barrier masterbatch, then three-layer co-extrusion, calendering stretching and heat setting are adopted to form multi-level bending penetration path.The obtained material has higher oxygen and water vapor barrier property, interlayer bonding strength, dimensional stability and biodegradability, while maintaining higher bamboo powder content and biodegradability, the oxygen barrier property, water vapor barrier property, interlayer bonding strength, dimensional stability and co-extrusion processing stability of packaging material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester biodegradable plastics technology, specifically to a high-barrier bamboo powder biodegradable composite packaging material and its co-extrusion molding method. Background Technology

[0002] With the development of green packaging and biodegradable materials, biodegradable packaging materials based on polylactic acid, biodegradable polyester, and natural plant fibers are gradually being used. Bamboo powder has the advantages of wide availability, renewability, low cost, and good natural degradation. Adding bamboo powder to biodegradable resin can reduce the amount of petrochemical raw materials used and increase the biomass content of the material. However, bamboo powder contains many hydrophilic hydroxyl groups on its surface, making it easy to absorb moisture. Moreover, the interfacial compatibility between bamboo powder and hydrophobic resins such as polylactic acid and biodegradable polyester is poor. When bamboo powder is directly added to the resin, it is prone to agglomeration, interfacial detachment, and microporous defects. This allows water vapor, oxygen, and odor molecules to quickly penetrate along the interfacial gaps between the bamboo powder and the resin, making it difficult for the resulting packaging material to simultaneously achieve a high bamboo powder content, mechanical strength, and barrier properties.

[0003] Existing biodegradable packaging materials typically improve barrier properties by adding nano-clay, cellulose, or inorganic fillers. However, these barrier components tend to agglomerate in the resin, and their layers or fibers lack stable spatial arrangement, making it difficult to form continuous and tortuous permeation-blocking paths. Furthermore, existing single-layer extrusion molding methods usually mix bamboo powder, barrier fillers, and matrix resin simultaneously. The hygroscopicity of bamboo powder and the dispersibility of the barrier fillers interact, easily reducing melt flow stability and making it difficult to concentrate bamboo powder and barrier components in the load-bearing layer. This leads to a decrease in material toughness and processing performance with increased barrier filler usage. Therefore, it is necessary to provide a high-barrier bamboo powder biodegradable composite packaging material and its co-extrusion molding method. This method involves hydrophobic treatment of bamboo powder, construction of a nano-clay and nano-cellulose composite barrier structure, and the use of a multi-layer co-extrusion structure (surface layer-core layer-surface layer) to achieve a layered configuration of bamboo powder's load-bearing and gas-barrier functions. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a high-barrier bamboo powder biodegradable composite packaging material and its co-extrusion molding method, thereby solving the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a high-barrier bamboo powder biodegradable composite packaging material, comprising the following components by weight: 45-70 parts polylactic acid, 15-35 parts biodegradable polyester, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts nano clay, 1-6 parts nano cellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant. The biodegradable polyester is poly(butylene adipate / terephthalate).

[0006] To further optimize this technical solution, the bamboo powder is composed of coarse bamboo powder and fine bamboo powder. The particle size of the coarse bamboo powder is 80-150 mesh, and the particle size of the fine bamboo powder is 200-400 mesh. The mass ratio of the coarse bamboo powder to the fine bamboo powder is 1:1 to 1:3. The coarse bamboo powder is used to form a bamboo skeleton and limit material shrinkage, while the fine bamboo powder fills the gaps between the coarse bamboo powder, polylactic acid, and biodegradable polyester.

[0007] To further optimize this technical solution, the thermoplastic starch is obtained by plasticizing native starch, glycerol and water, wherein the mass ratio of native starch, glycerol and water is 100:20-35:8-18; The plasticizing process includes mixing native starch, glycerol and water, stirring at 70-95°C for 20-50 minutes, and then shearing plasticizing at 100-125°C to destroy the original crystalline structure of the native starch granules and form a continuous plasticized phase. The original starch is one or more of corn starch, tapioca starch or potato starch, and the moisture content of the resulting thermoplastic starch is 1% to 5%.

[0008] To further optimize this technical solution, the nano-clay is nano-montmorillonite, with a sheet thickness of 1-5 nanometers, a sheet transverse dimension of 80-500 nanometers, and a sheet aspect ratio of 30-200. The nano-montmorillonite is dispersed in the composite packaging material in the form of single layers and layer clusters consisting of 2 to 8 layers, with the spacing between adjacent layers in the layer cluster being 1.5 to 4 nanometers.

[0009] To further optimize this technical solution, the nanocellulose is cellulose nanofiber, the diameter of which is 5-30 nanometers, the length of which is 100-800 nanometers, the aspect ratio of which is 10-100, and the hydroxyl content of which is 5-12 mmol / g. A portion of the cellulose nanofibers is located between the nano-clay sheets, while another portion is distributed in the interface region between bamboo powder and polylactic acid, and between bamboo powder and biodegradable polyester.

[0010] To further optimize this technical solution, the epoxidized soybean oil and citric acid together form an interface regulating component, and the epoxy value of the epoxidized soybean oil is 5% to 8%. The preparation process of the interface-modifying component includes: heating epoxidized soybean oil to 70-100°C, adding citric acid and stirring for 10-30 minutes to uniformly disperse the citric acid in the epoxidized soybean oil, while retaining some unreacted epoxy and carboxyl groups.

[0011] To further optimize this technical solution, the plant wax is one or more of carnauba wax, rice bran wax, or beeswax, and the melting point of the plant wax is 60–90°C. The plant wax includes a first part of plant wax for coating bamboo powder and a second part of plant wax directly dispersed in a resin matrix formed by polylactic acid and biodegradable polyester, with a mass ratio of the first part of plant wax to the second part of plant wax of 1:0.3 to 1:1.5. The first part of plant wax forms a coating layer with an average thickness of 0.1–2 micrometers on the surface of bamboo powder, and the second part of plant wax exists as a dispersed phase with a particle size of no more than 5 micrometers within the continuous phase formed by polylactic acid and biodegradable polyester.

[0012] To further optimize this technical solution, the melt flow rate of the polylactic acid under the conditions of 190℃ and 2.16 kg load is 3-15 g / 10 min, and the melt flow rate of the biodegradable polyester under the same test conditions is 2-10 g / 10 min, and the difference between the melt flow rates of the two is not greater than 8 g / 10 min.

[0013] To further optimize this technical solution, the nano-clay sheets in the composite packaging material are oriented along the surface of the packaging material, and the number of sheets with an angle of no more than 30° between the sheet plane and the surface of the packaging material accounts for more than 60% of the total number of nano-clay sheets. The amount of bamboo powder with an angle of no more than 45° between its length direction and the surface of the packaging material accounts for more than 55% of the total amount of bamboo powder. The oriented structure is formed by extrusion casting, blown film stretching, or sheet calendering, so that the nano-clay sheets and bamboo powder are staggered in the thickness direction of the material.

[0014] A co-extrusion molding method for a high-barrier bamboo powder biodegradable composite packaging material, based on the above-mentioned composite packaging material, includes the following specific steps: S1. Weigh each component according to the formula, and dry and surface treat the bamboo powder, starch and filler; S2. Nano-clay and nano-cellulose are compositely dispersed to prepare a high-barrier masterbatch for surface layer. S3. Mix the treated bamboo powder, thermoplastic starch and matrix resin to obtain the core layer composite masterbatch. S4. Melt the surface masterbatch and core masterbatch separately, and control the melt temperature, pressure and flow state; S5. Combine the two surface melts with the core melt and co-extrude them to form a surface-core-surface structure. S6. Calender, stretch, cool and heat set the co-extruded material, and complete the trimming and winding.

[0015] Compared with the prior art, the present invention provides a high-barrier bamboo powder biodegradable composite packaging material and its co-extrusion molding method, which has the following beneficial effects: This high-barrier bamboo powder biodegradable composite packaging material and its co-extrusion molding method reduce the moisture content of bamboo powder of different particle sizes and seal its surface water absorption channels by drying, treating with citric acid, and coating with plant wax. Simultaneously, epoxidized soybean oil and citric acid improve the interfacial bonding between bamboo powder, thermoplastic starch, and biodegradable resin, reducing internal porosity and interfacial cracks. Furthermore, by pre-forming a layered-fiber composite barrier powder from nano-clay and nanocellulose, the nanocellulose connects and separates the nano-clay layers, reducing the agglomeration of the barrier components. Further, a three-layer co-extrusion structure of surface layer-core layer-surface layer is adopted, in which the composite barrier powder is concentrated on both surface layers, and the bamboo powder and thermoplastic starch are concentrated in the core layer. Through co-extrusion shearing, calendering and heat setting, the nano-clay sheets and bamboo powder are oriented along the surface of the packaging material, thereby forming a multi-level tortuous penetration path in the thickness direction of the material. While maintaining a high bamboo powder content and biodegradability, the oxygen barrier, water vapor barrier, interlayer bonding strength, dimensional stability and co-extrusion processing stability of the packaging material are improved. Attached Figure Description

[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic flowchart of a co-extrusion molding method for a high-barrier bamboo powder biodegradable composite packaging material proposed in this invention. Detailed Implementation

[0018] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0019] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single embodiment or an embodiment selectively excluded from other embodiments.

[0021] A high-barrier bamboo powder biodegradable composite packaging material, by weight, comprises the following components: 45-70 parts polylactic acid, 15-35 parts biodegradable polyester, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts nano clay, 1-6 parts nanocellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant.

[0022] The biodegradable polyester is polybutylene adipate / terephthalate (PBAT), primarily used to improve the toughness of the composite material of polylactic acid and bamboo powder, preventing the packaging material from becoming too brittle. Bamboo powder, as a biomass filler, has a moisture content controlled below 3% to reduce problems such as bubbles, voids, and interface detachment during melt processing. Nanoclay and nanocellulose together constitute the main barrier components. Nanoclay forms layered barrier pathways within the resin, extending the penetration distance of oxygen, water vapor, and odor molecules; nanocellulose fills the tiny gaps between bamboo powder and resin, forming a dense fiber network and reducing internal porosity. The combined use of these two components is more effective in improving oxygen barrier performance than adding ordinary inorganic fillers alone. Plant waxes are mainly used to reduce the water absorption and water vapor permeability of the packaging material surface. Epoxidized soybean oil improves the material's flexibility and enhances the interfacial bonding between bamboo powder, starch, and polylactic acid; citric acid promotes a more stable interfacial structure between the starch, bamboo powder, and resin phases, reducing porosity caused by differences in hydrophilicity. Talc is used to improve dimensional stability and thermoforming properties, stearic acid is used to improve the dispersibility of bamboo powder and other fillers in resin, and antioxidants are used to reduce thermo-oxidative aging during melt processing.

[0023] The bamboo powder is bamboo powder that has undergone drying, acidification, and hydrophobic coating treatment. The treatment process includes: drying the bamboo powder at 80–105°C for 2–6 hours to reduce the moisture content to below 2%; mixing the dried bamboo powder with a 2%–6% citric acid aqueous solution, followed by heat treatment at 110–140°C for 20–60 minutes; and then mixing the heat-treated bamboo powder with molten plant wax to form a continuous or discontinuous hydrophobic coating layer on the surface of the bamboo powder. Through the above treatment, some hydroxyl groups on the surface of the bamboo powder are esterified with citric acid, and the plant wax seals the water absorption channels on the surface of the bamboo powder, thereby reducing the hygroscopic pores formed by the bamboo powder in the resin matrix. The plant wax used for coating the surface of the bamboo powder accounts for 40%–75% of the total mass of the plant wax.

[0024] The bamboo powder is composed of coarse bamboo powder and fine bamboo powder. The coarse bamboo powder has a particle size of 80-150 mesh, and the fine bamboo powder has a particle size of 200-400 mesh. The mass ratio of coarse bamboo powder to fine bamboo powder is 1:1 to 1:3. The coarse bamboo powder is used to form a bamboo skeleton and limit material shrinkage, while the fine bamboo powder fills the gaps between the coarse bamboo powder, polylactic acid, and biodegradable polyester. By using bamboo powder with two different particle sizes, a stacked structure of inter-sized particles is formed, reducing the probability of single-size bamboo powder forming continuous channels in the resin matrix. The average aspect ratio of the bamboo powder is 1.5-4.5, and the content of powder with a particle size smaller than 400 mesh does not exceed 10% of the total mass of the bamboo powder to avoid excessive adsorption of plasticizing components by excessively fine bamboo powder, which could lead to an abnormal increase in melt viscosity.

[0025] The thermoplastic starch is obtained by plasticizing native starch, glycerol, and water, wherein the mass ratio of native starch, glycerol, and water is 100:20-35:8-18. The plasticizing process includes mixing native starch, glycerol, and water, stirring at 70-95°C for 20-50 minutes, and then shear plasticizing at 100-125°C, which destroys the original crystalline structure of the native starch granules and forms a continuous plasticized phase. The native starch is one or more of corn starch, tapioca starch, or potato starch, and the moisture content of the obtained thermoplastic starch is 1%-5%. Limiting the composition and plasticization state of the thermoplastic starch within the above range prevents the direct addition of unplasticized starch granules, which could lead to brittle defects and water vapor permeation channels in the material.

[0026] The nano-clay is nano-montmorillonite, with a sheet thickness of 1–5 nanometers, a lateral dimension of 80–500 nanometers, and an aspect ratio of 30–200. The nano-montmorillonite is dispersed in the composite packaging material as single sheets and sheet clusters consisting of 2–8 sheets, with a spacing of 1.5–4 nanometers between adjacent sheets within a cluster. The number of single sheets and sheet clusters consisting of no more than 5 sheets accounts for more than 60% of the total number of nano-montmorillonite sheets, reducing the presence of large-sized agglomerated particles. This structural state requires permeating molecules to bypass multiple staggered sheets, rather than directly penetrating the composite material along the interfacial gap between bamboo powder and resin.

[0027] The nano-clay and nanocellulose are pre-formed into a sheet-fiber composite barrier powder. The preparation process of the sheet-fiber composite barrier powder includes: dispersing nanocellulose in water to form a nanocellulose dispersion with a mass concentration of 0.5% to 2.5%; adding nanoclay to the nanocellulose dispersion; shearing and dispersing at a pH of 4 to 6 and a temperature of 20 to 50°C for 20 to 60 minutes; and then spray drying or vacuum drying. After drying, nanocellulose adheres to the surface and edges of the nanoclay sheets, forming a fibrous connection structure between adjacent nanoclay sheets. By first forming the composite barrier powder and then mixing it with resin and bamboo powder, the independent agglomeration phenomenon that occurs when nanoclay and nanocellulose are added separately can be reduced.

[0028] The nanocellulose is cellulose nanofiber with a diameter of 5–30 nm, a length of 100–800 nm, an aspect ratio of 10–100, and a surface hydroxyl content of 5–12 mmol / g. A portion of the cellulose nanofiber is located between the nanoclay layers, while another portion is distributed in the interfacial regions between bamboo powder and polylactic acid, and between bamboo powder and biodegradable polyester. By limiting the size and distribution of the nanocellulose, it can fill the tiny gaps at the bamboo powder interface, while avoiding the use of excessively large cellulose fibers that would cause surface roughness or the formation of new interfacial defects in the composite material.

[0029] The epoxidized soybean oil and citric acid together form an interface-modifying component, wherein the epoxy value of the epoxidized soybean oil is 5%–8%. The preparation process of the interface-modifying component includes: heating the epoxidized soybean oil to 70–100°C, adding citric acid and stirring for 10–30 minutes to uniformly disperse the citric acid in the epoxidized soybean oil, while retaining some unreacted epoxy and carboxyl groups; subsequently, the obtained interface-modifying component is added to a mixture of polylactic acid, biodegradable polyester, bamboo powder, and thermoplastic starch. During melt processing, the residual epoxy groups undergo ring-opening bonding with the hydroxyl groups on the surface of bamboo powder, thermoplastic starch, and nanocellulose, while the residual carboxyl groups interact with the end groups of polylactic acid and biodegradable polyester, thereby forming a continuous interfacial transition layer between the hydrophilic component and the hydrophobic resin.

[0030] The plant wax is one or more of carnauba wax, rice bran wax, or beeswax, and its melting point is 60–90°C. The plant wax comprises a first portion for coating bamboo powder and a second portion dispersed directly in the resin matrix, with a mass ratio of 1:0.3 to 1:1.5. The first portion of plant wax forms a coating layer with an average thickness of 0.1–2 micrometers on the surface of the bamboo powder, while the second portion exists as a dispersed phase with a particle size no greater than 5 micrometers within the continuous phase formed by polylactic acid and biodegradable polyester. Using a segmented plant wax configuration reduces the hygroscopicity of the bamboo powder and seals the micro-permeability channels in the resin matrix, avoiding the problem of insufficient coating on the bamboo powder surface that would occur if all the plant wax were added directly to the resin.

[0031] The polylactic acid (PLA) exhibits a melt flow rate of 3–15 g / 10 min at 190°C and a load of 2.16 kg, while the biodegradable polyester exhibits a melt flow rate of 2–10 g / 10 min under the same test conditions. The difference between the two melt flow rates is no greater than 8 g / 10 min. By limiting the flow property differences between the two matrix resins, the biodegradable polyester can be distributed as a dispersed phase with an average size of 0.2–3 micrometers within the continuous PLA phase. This avoids the formation of excessively large flexible polyester regions that would reduce gas barrier properties. Simultaneously, this dispersed phase mitigates the brittleness resulting from the PLA and bamboo powder composite.

[0032] The nano-clay sheets in the composite packaging material are oriented along the surface of the packaging material, with at least 60% of the nano-clay sheets having an angle of no more than 30° between their plane and the surface of the packaging material. Similarly, at least 55% of the bamboo powder has an angle of no more than 45° between its length and the surface of the packaging material. This oriented structure is formed through extrusion casting, blown film stretching, or sheet calendering, causing the nano-clay sheets and bamboo powder to be staggered in the thickness direction of the material, thus creating a multi-level, tortuous permeation path composed of nano-clay sheets, nanocellulose, and bamboo powder.

[0033] See Figure 1 A co-extrusion molding method for a high-barrier bamboo powder biodegradable composite packaging material includes the following steps: S1. Based on the overall formulation of the composite packaging material, bamboo powder, thermoplastic starch and various barrier components are pretreated. Bamboo powder was divided into coarse bamboo powder with a particle size of 80-150 mesh and fine bamboo powder with a particle size of 200-400 mesh, with the mass ratio of coarse to fine bamboo powder controlled at 1:1 to 1:3. The two types of bamboo powder were mixed and dried at 80-105℃ for 2-6 hours to ensure the moisture content of the bamboo powder did not exceed 2%. The dried bamboo powder was mixed with a citric acid aqueous solution and heat-treated at 110-140℃ for 20-60 minutes. Then, 40%-75% of the plant wax from the formula was added for coating, forming a hydrophobic layer on the surface of the bamboo powder. Thermoplastic starch, nano-clay, nanocellulose, and talc were dried separately, ensuring the moisture content of the thermoplastic starch did not exceed 3%, and the moisture content of the nano-clay, nanocellulose, and talc did not exceed 1%.

[0034] S2. Based on the pretreated nano-clay and nano-cellulose in S1, prepare a composite barrier masterbatch for co-extrusion surface layer. Nanocellulose is added to water to form a nanocellulose dispersion with a mass concentration of 0.5%–2.5%. Nanoclay is then added, and the mixture is sheared and dispersed at 1000–3000 rpm for 20–60 minutes at a pH of 4–6 and a temperature of 20–50°C, allowing the nanocellulose to adhere to the surface and edges of the nanoclay sheets. The resulting dispersion is spray-dried or vacuum-dried to obtain a sheet-fiber composite barrier powder. This composite barrier powder is mixed with polylactic acid (PLA) for the surface layer, biodegradable polyester, epoxidized soybean oil, remaining plant waxes, and a portion of antioxidants. The mixture is then melt-kneaded in a twin-screw extruder. The temperatures in each zone of the twin-screw extruder are sequentially controlled at 145–155°C, 155–165°C, 160–175°C, and 165–175°C, with the screw speed controlled at 100–250 rpm. After mixing, the mixture is extruded, cooled, and pelletized to obtain the composite barrier masterbatch.

[0035] S3. Based on the bamboo powder and thermoplastic starch that have undergone surface treatment in S1, prepare a bamboo powder composite masterbatch for use in co-extrusion core layer; Surface-treated bamboo powder, thermoplastic starch, talc, and stearic acid are premixed, and then polylactic acid, biodegradable polyester, epoxidized soybean oil, residual citric acid, and residual antioxidants for the core layer are added to form a core layer mixture. The core layer mixture is added to a twin-screw extruder and melt-mixed at 145–175°C, with the screw speed controlled at 80–220 rpm and the average residence time of the material in the twin-screw extruder controlled at 1–4 minutes. During the mixing process, polylactic acid and biodegradable polyester first form a continuous resin phase, and then bamboo powder and thermoplastic starch are dispersed within this continuous resin phase. Epoxidized soybean oil and citric acid form an interfacial transition zone between the bamboo powder, thermoplastic starch, and resin. The mixed material is then subjected to vacuum degassing, melt filtration, extrusion, cooling, and pelletizing to obtain a bamboo powder composite masterbatch. The vacuum degree in the vacuum degassing section is controlled at -0.06–-0.095 MPa, and the melt filter mesh size is 80–150 mesh.

[0036] S4. The composite barrier masterbatch prepared based on S2 and the bamboo powder composite masterbatch prepared based on S3 form the surface melt and the core melt, respectively. The composite barrier masterbatch is added to the first and second surface extruders, while the bamboo powder composite masterbatch is added to the core extruder. The heating temperatures of the first and second surface extruders are controlled sequentially from the feed end to the discharge end at 150–160℃, 160–170℃, 165–180℃, and 170–185℃; the heating temperature of the core extruder is controlled sequentially from the feed end to the discharge end at 145–155℃, 150–165℃, 155–170℃, and 160–175℃. The outlet temperature difference between the two surface melts is controlled to be no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is controlled to be no greater than 10℃. The screw speeds of the first and second surface extruders are controlled at 60–180 rpm, and the screw speed of the core extruder is controlled at 50–150 rpm, so that the melt pressure of each layer is stabilized at 5–15 MPa, avoiding interface fluctuations caused by excessive differences in melt temperature or flow rate between adjacent layers.

[0037] S5. Based on the surface melt and core melt formed in S4, construct a three-layer co-extrusion structure with the surface layer, core layer and surface layer stacked in sequence. The surface melt from the first surface extruder, the core melt from the core extruder, and the surface melt from the second surface extruder are respectively fed to a three-layer co-extrusion distributor, where the three melts are combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is controlled at 10–20:60–80:10–20, and the thickness deviation between the two surface layers does not exceed 10% of the average surface layer thickness. The combined three-layer melt is extruded through a co-extrusion die at a temperature of 165–180℃, with the die gap controlled at 0.3–1.5 mm. By adjusting the distributor channel width and the feed rate of each extruder, the nano-clay sheets in the surface layer are subjected to shearing action along the extrusion direction and arranged parallel to the material surface. At the same time, the coarse bamboo powder and fine bamboo powder in the core layer are mutually filled, forming a layered structure in which the bamboo powder core layer is sealed by barrier layers on both sides.

[0038] S6. Based on the three-layer co-extruded material formed by S5, the flakes and bamboo powder in each layer are directionally cured and dimensionally stabilized. The three-layer melt output from the co-extrusion die is introduced into cooling rollers at a temperature of 20–40°C for calendering and cooling. The linear speed of the cooling rollers is controlled at 2–15 m / min, and the calendering gap is set to 0.1–1.2 mm according to the target thickness of the packaging material. During the cooling process, the three-layer material is subjected to a longitudinal stretch of 1.2–2.5 times, causing the plane of the nano-clay sheets and the length direction of the bamboo powder to tend to be parallel to the surface of the packaging material, thereby forming a staggered penetration barrier structure in the thickness direction of the material. The pre-cooled material is then heat-set at 70–95°C for 20–90 seconds, and then cooled to below 40°C at a cooling rate of 5–20°C / min. After heat setting, the number of nano-clay sheets with an angle of no more than 30° to the surface of the packaging material accounts for more than 60% of the total number of nano-clay sheets, and the number of bamboo powder with an angle of no more than 45° to the surface of the packaging material accounts for more than 55% of the total number of bamboo powder. Finally, after edge trimming, traction and winding, a high-barrier bamboo powder biodegradable composite packaging material is obtained.

[0039] In the following examples and comparative examples, the biodegradable polyester is explicitly selected as polybutylene adipate / terephthalate, i.e., PBAT; the native starch is corn starch; the plant wax is carnauba wax; the nano clay is nano-montmorillonite; the nanocellulose is cellulose nanofiber; the antioxidant is antioxidant 1010; the sheet-fiber composite barrier powder is spray-dried; and the composite packaging material is sheet calendering.

[0040] Example 1: This embodiment provides a high-barrier bamboo powder biodegradable composite packaging material, which, by weight, includes the following components: 45 parts polylactic acid, 15 parts PBAT, 10 parts bamboo powder, 5 parts thermoplastic starch, 2 parts nano-montmorillonite, 1 part cellulose nanofiber, 1 part carnauba wax, 1 part epoxidized soybean oil, 0.3 parts citric acid, 1 part talc, 0.3 parts stearic acid, and 0.1 parts antioxidant 1010.

[0041] The bamboo powder is composed of coarse bamboo powder and fine bamboo powder. The coarse bamboo powder has a particle size of 115 mesh, and the fine bamboo powder has a particle size of 300 mesh. The mass ratio of coarse bamboo powder to fine bamboo powder is 1:2. The average aspect ratio of the bamboo powder is 3, and the content of powder with a particle size smaller than 400 mesh in the bamboo powder does not exceed 10% of the total mass of the bamboo powder.

[0042] The thermoplastic starch is obtained by plasticizing corn starch, glycerol, and water, with a mass ratio of corn starch, glycerol, and water of 100:27.5:13. The corn starch, glycerol, and water are mixed and stirred at 82.5°C for 35 minutes, followed by shear plasticization at 112.5°C to obtain thermoplastic starch with a moisture content of 3%.

[0043] The nano-montmorillonite has a sheet thickness of 3 nanometers, a lateral dimension of 290 nanometers, and an aspect ratio of 115. The nano-montmorillonite is dispersed in the form of single sheets and sheet clusters consisting of 5 sheets, with a spacing of 2.75 nanometers between adjacent sheets within a sheet cluster; single sheets and sheet clusters consisting of no more than 5 sheets account for more than 60% of the total number of nano-montmorillonite sheets.

[0044] The cellulose nanofibers have a diameter of 17.5 nm, a length of 450 nm, an aspect ratio of 55, and a surface hydroxyl content of 8.5 mmol / g. A portion of the cellulose nanofibers is located between nano-montmorillonite sheets, and another portion is located at the interface between bamboo powder and polylactic acid, and between bamboo powder and PBAT.

[0045] The epoxy value of the epoxidized soybean oil is 6.5%. The epoxidized soybean oil is heated to 85°C, citric acid is added and stirred for 20 minutes to obtain the interface conditioning component.

[0046] The melting point of the carnauba wax is 75°C. The carnauba wax comprises a first part of carnauba wax coating bamboo powder and a second part of carnauba wax dispersed in a resin matrix, with a mass ratio of the first part of carnauba wax to the second part of carnauba wax of 1:0.9. The first part of carnauba wax forms a continuous coating layer with an average thickness of 1.05 micrometers on the surface of the bamboo powder, and the second part of carnauba wax exists as a dispersed phase with a particle size of no more than 5 micrometers in the resin phase formed by polylactic acid and PBAT.

[0047] The polylactic acid exhibits a melt flow rate of 9 g / 10 min at 190 °C and a load of 2.16 kg, while PBAT exhibits a melt flow rate of 6 g / 10 min under the same conditions. PBAT is distributed as a dispersed phase with an average size of 1.6 μm within the continuous polylactic acid phase.

[0048] The co-extrusion molding method of this embodiment includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours to ensure the bamboo powder moisture content is no higher than 2%. Mix the dried bamboo powder with a 4% citric acid aqueous solution, heat-treat at 125℃ for 40 minutes, then add 57.5% (by mass) of carnauba wax, and mix and coat at 75℃. Dry thermoplastic starch to a moisture content no higher than 3%, and dry nano-montmorillonite, cellulose nanofibers, and talc powder separately to a moisture content no higher than 1%.

[0049] S2. Cellulose nanofibers were added to water to prepare a 1.5% (w / w) cellulose nanofiber dispersion. Nano-montmorillonite was then added, and the dispersion was sheared at 2000 rpm for 40 minutes at a pH of 5 and a temperature of 35°C. The resulting dispersion was spray-dried to obtain a layer-fiber composite barrier powder. The layer-fiber composite barrier powder was mixed with polylactic acid (PLA), PBAT, epoxidized soybean oil, remaining carnauba wax, and a portion of antioxidant 1010 for the surface layer, and melt-blended in a twin-screw extruder. The temperatures of the twin-screw extruder zones were 150°C, 160°C, 167.5°C, and 170°C, respectively, and the screw speed was 175 rpm. After blending, the mixture was extruded, cooled, and pelletized to obtain the composite barrier masterbatch.

[0050] S3. Surface-treated bamboo powder, thermoplastic starch, talc, and stearic acid are premixed, and then polylactic acid, PBAT, epoxidized soybean oil, residual citric acid, and residual antioxidant 1010 are added to form the core layer mixture. The core layer mixture is added to a twin-screw extruder and melt-mixed at 160°C, with a screw speed of 150 rpm and an average residence time of 2.5 minutes. The mixed material is then extruded, cooled, and pelletized after vacuum degassing and melt filtration to obtain bamboo powder composite masterbatch; the vacuum degree of the vacuum degassing section is -0.0775 MPa, and the melt filter mesh size is 115 mesh.

[0051] S4. Add the composite barrier masterbatch to the first and second surface extruders respectively, and add the bamboo powder composite masterbatch to the core extruder. The heating temperatures of the first and second surface extruders from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively; the heating temperatures of the core extruder from the feed end to the discharge end are 150℃, 157.5℃, 162.5℃, and 167.5℃ respectively. The outlet temperature difference between the two surface melts is no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is no greater than 10℃. The screw speed of the first and second surface extruders is 120 rpm, the screw speed of the core extruder is 100 rpm, and the melt pressure of each layer is 10 MPa.

[0052] S5. The first surface layer melt, core layer melt, and second surface layer melt are respectively fed to the three-layer co-extrusion distributor and combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is 15:70:15, and the thickness deviation between the two surface layers does not exceed 10% of the average thickness of the surface layer. The three-layer melt is extruded through a co-extrusion die at a temperature of 172.5℃ with a die gap of 0.9 mm.

[0053] S6. The three-layer co-extruded material is introduced between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. The three-layer material is subjected to a longitudinal stretch of 1.85 times, and heat-set at 82.5°C for 55 seconds. It is then cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the composite packaging material is obtained. In the obtained material, the number of nano-montmorillonite sheets with an angle of no more than 30° between the sheet plane and the surface of the packaging material accounts for more than 60% of the total number of nano-montmorillonite sheets, and the number of bamboo powders with an angle of no more than 45° between their length direction and the surface of the packaging material accounts for more than 55% of the total number of bamboo powders.

[0054] Example 2: This embodiment provides a high-barrier bamboo powder biodegradable composite packaging material, which, by weight, includes the following components: 57.5 parts polylactic acid, 25 parts PBAT, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts nano-montmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, and 0.45 parts antioxidant 1010.

[0055] The types, structural parameters, and pretreatment parameters of the bamboo powder, thermoplastic starch, nano-montmorillonite, cellulose nanofibers, epoxidized soybean oil, carnauba wax, polylactic acid, and PBAT are the same as in Example 1.

[0056] The co-extrusion molding method of this embodiment includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours to ensure the bamboo powder moisture content is no higher than 2%. Mix the dried bamboo powder with a 4% citric acid aqueous solution, heat-treat at 125℃ for 40 minutes, then add 57.5% (by mass) of carnauba wax, and mix and coat at 75℃. Dry thermoplastic starch to a moisture content no higher than 3%, and dry nano-montmorillonite, cellulose nanofibers, and talc powder separately to a moisture content no higher than 1%.

[0057] S2. Cellulose nanofibers were added to water to prepare a 1.5% (w / w) cellulose nanofiber dispersion. Nano-montmorillonite was then added, and the dispersion was sheared at 2000 rpm for 40 minutes at a pH of 5 and a temperature of 35°C. The resulting dispersion was spray-dried to obtain a layer-fiber composite barrier powder. The layer-fiber composite barrier powder was mixed with polylactic acid (PLA), PBAT, epoxidized soybean oil, remaining carnauba wax, and a portion of antioxidant 1010 for the surface layer, and melt-blended in a twin-screw extruder. The temperatures of the twin-screw extruder zones were 150°C, 160°C, 167.5°C, and 170°C, respectively, and the screw speed was 175 rpm. After blending, the mixture was extruded, cooled, and pelletized to obtain the composite barrier masterbatch.

[0058] S3. Surface-treated bamboo powder, thermoplastic starch, talc, and stearic acid are premixed, and then polylactic acid, PBAT, epoxidized soybean oil, residual citric acid, and residual antioxidant 1010 are added to form the core layer mixture. The core layer mixture is added to a twin-screw extruder and melt-mixed at 160°C, with a screw speed of 150 rpm and an average residence time of 2.5 minutes. The mixed material is then extruded, cooled, and pelletized after vacuum degassing and 115-mesh melt filtration to obtain bamboo powder composite masterbatch. The vacuum degree of the vacuum degassing section is -0.0775 MPa.

[0059] S4. Add the composite barrier masterbatch to the first and second surface extruders respectively, and add the bamboo powder composite masterbatch to the core extruder. The heating temperatures of the first and second surface extruders from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively; the heating temperatures of the core extruder from the feed end to the discharge end are 150℃, 157.5℃, 162.5℃, and 167.5℃ respectively. The outlet temperature difference between the two surface melts is no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is no greater than 10℃. The screw speed of both surface extruders is 120 rpm, the screw speed of the core extruder is 100 rpm, and the melt pressure of each layer is 10 MPa.

[0060] S5. The first surface layer melt, core layer melt, and second surface layer melt are conveyed to the three-layer co-extrusion distributor and combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is 15:70:15, and the thickness deviation between the two surface layers does not exceed 10% of the average thickness of the surface layer. The three-layer melt is extruded through a co-extrusion die at a temperature of 172.5℃ with a die gap of 0.9 mm.

[0061] S6. The three-layer co-extruded material is introduced between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. The three-layer material is subjected to a longitudinal stretch of 1.85 times, heat-set at 82.5°C for 55 seconds, and then cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the composite packaging material is obtained. The orientation state of the nano-montmorillonite sheets and bamboo powder in the obtained material is the same as in Example 1.

[0062] Example 3: This embodiment provides a high-barrier bamboo powder biodegradable composite packaging material, which, by weight, includes the following components: 70 parts polylactic acid, 35 parts PBAT, 30 parts bamboo powder, 18 parts thermoplastic starch, 8 parts nano-montmorillonite, 6 parts cellulose nanofibers, 5 parts carnauba wax, 5 parts epoxidized soybean oil, 2 parts citric acid, 6 parts talc, 1.5 parts stearic acid, and 0.8 parts antioxidant 1010.

[0063] The types, structural parameters, and pretreatment parameters of the bamboo powder, thermoplastic starch, nano-montmorillonite, cellulose nanofibers, epoxidized soybean oil, carnauba wax, polylactic acid, and PBAT are the same as in Example 1.

[0064] The co-extrusion molding method of this embodiment includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours to ensure the bamboo powder moisture content is no higher than 2%. Mix the dried bamboo powder with a 4% citric acid aqueous solution, heat-treat at 125℃ for 40 minutes, then add 57.5% (by mass) of carnauba wax, and mix and coat at 75℃. Dry thermoplastic starch to a moisture content no higher than 3%, and dry nano-montmorillonite, cellulose nanofibers, and talc powder separately to a moisture content no higher than 1%.

[0065] S2. Cellulose nanofibers were added to water to prepare a 1.5% (w / w) cellulose nanofiber dispersion. Nano-montmorillonite was then added, and the dispersion was sheared at 2000 rpm for 40 minutes at a pH of 5 and a temperature of 35°C. The resulting dispersion was spray-dried to obtain a layer-fiber composite barrier powder. The layer-fiber composite barrier powder was mixed with polylactic acid (PLA), PBAT, epoxidized soybean oil, remaining carnauba wax, and a portion of antioxidant 1010 for the surface layer, and melt-blended in a twin-screw extruder. The temperatures of the twin-screw extruder zones were 150°C, 160°C, 167.5°C, and 170°C, respectively, and the screw speed was 175 rpm. After blending, the mixture was extruded, cooled, and pelletized to obtain the composite barrier masterbatch.

[0066] S3. Surface-treated bamboo powder, thermoplastic starch, talc, and stearic acid are premixed, and then polylactic acid, PBAT, epoxidized soybean oil, residual citric acid, and residual antioxidant 1010 are added to form the core layer mixture. The core layer mixture is added to a twin-screw extruder and melt-mixed at 160°C, with a screw speed of 150 rpm and an average residence time of 2.5 minutes. The mixed material is then extruded, cooled, and pelletized after vacuum degassing and 115-mesh melt filtration to obtain bamboo powder composite masterbatch. The vacuum degree of the vacuum degassing section is -0.0775 MPa.

[0067] S4. Add the composite barrier masterbatch to the first and second surface extruders respectively, and add the bamboo powder composite masterbatch to the core extruder. The heating temperatures of the first and second surface extruders from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively; the heating temperatures of the core extruder from the feed end to the discharge end are 150℃, 157.5℃, 162.5℃, and 167.5℃ respectively. The outlet temperature difference between the two surface melts is no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is no greater than 10℃. The screw speed of both surface extruders is 120 rpm, the screw speed of the core extruder is 100 rpm, and the melt pressure of each layer is 10 MPa.

[0068] S5. The first surface layer melt, core layer melt, and second surface layer melt are conveyed to the three-layer co-extrusion distributor and combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is 15:70:15, and the thickness deviation between the two surface layers does not exceed 10% of the average thickness of the surface layer. The three-layer melt is extruded through a co-extrusion die at a temperature of 172.5℃ with a die gap of 0.9 mm.

[0069] S6. The three-layer co-extruded material is introduced between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. The three-layer material is subjected to a longitudinal stretch of 1.85 times, heat-set at 82.5°C for 55 seconds, and then cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the composite packaging material is obtained. The orientation state of the nano-montmorillonite sheets and bamboo powder in the obtained material is the same as in Example 1.

[0070] Comparative Example 1: The difference between this comparative example and Example 2 is that nano-montmorillonite and cellulose nanofibers are not added.

[0071] The composite packaging material in this comparative example, by weight, includes the following components: 57.5 parts polylactic acid, 25 parts PBAT, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, and 0.45 parts antioxidant 1010.

[0072] The co-extrusion molding method of this comparative example includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours to ensure the bamboo powder moisture content is no higher than 2%. Mix the dried bamboo powder with a 4% (w / w) citric acid aqueous solution, heat-treat at 125℃ for 40 minutes, then add 57.5% (w / w) of carnauba wax, and mix and coat at 75℃. Dry the thermoplastic starch to a moisture content no higher than 3%, and dry the talc powder to a moisture content no higher than 1%.

[0073] S2. Polylactic acid (PLA), PBAT, epoxidized soybean oil, remaining carnauba wax, and a portion of antioxidant 1010 for the surface layer are mixed and melt-blended in a twin-screw extruder. The temperatures of each zone of the twin-screw extruder are 150℃, 160℃, 167.5℃, and 170℃, respectively, and the screw speed is 175 rpm. After blending, the mixture is extruded, cooled, and pelletized to obtain the surface masterbatch.

[0074] S3. Surface-treated bamboo powder, thermoplastic starch, talc, and stearic acid are premixed, and then polylactic acid, PBAT, epoxidized soybean oil, residual citric acid, and residual antioxidant 1010 are added to form the core layer mixture. The core layer mixture is added to a twin-screw extruder and melt-mixed at 160°C, with a screw speed of 150 rpm and an average residence time of 2.5 minutes. The mixed material is then extruded, cooled, and pelletized after vacuum degassing and 115-mesh melt filtration to obtain bamboo powder composite masterbatch. The vacuum degree of the vacuum degassing section is -0.0775 MPa.

[0075] S4. Add the surface masterbatch to the first and second surface extruders respectively, and add the bamboo powder composite masterbatch to the core extruder. The heating temperatures of the first and second surface extruders from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively; the heating temperatures of the core extruder from the feed end to the discharge end are 150℃, 157.5℃, 162.5℃, and 167.5℃ respectively. The outlet temperature difference between the two surface melts is no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is no greater than 10℃. The screw speed of both surface extruders is 120 rpm, the screw speed of the core extruder is 100 rpm, and the melt pressure of each layer is 10 MPa.

[0076] S5. The first surface layer melt, core layer melt, and second surface layer melt are conveyed to the three-layer co-extrusion distributor and combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is 15:70:15, and the thickness deviation between the two surface layers does not exceed 10% of the average thickness of the surface layer. The three-layer melt is extruded through a co-extrusion die at a temperature of 172.5℃ with a die gap of 0.9 mm.

[0077] S6. The three-layer co-extruded material is introduced between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. The three-layer material is subjected to a longitudinal stretch of 1.85 times, and the material is heat-set at 82.5°C for 55 seconds. Then, it is cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the composite packaging material of Comparative Example 1 is obtained.

[0078] Comparative Example 2: The difference between this comparative example and Example 2 is that the bamboo powder is only dried, without citric acid acidification or carnauba wax pre-coating. The citric acid and carnauba wax in the formula are added directly during the masterbatch mixing stage.

[0079] The composite packaging material in this comparative example, by weight, comprises the following components: 57.5 parts polylactic acid, 25 parts PBAT, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts nano-montmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, and 0.45 parts antioxidant 1010.

[0080] The co-extrusion molding method of this comparative example includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours until the moisture content of the bamboo powder does not exceed 2%. Do not mix the dried bamboo powder with citric acid aqueous solution, and do not pre-coat the bamboo powder with carnauba wax. Dry the thermoplastic starch to a moisture content of no more than 3%, and dry the nano-montmorillonite, cellulose nanofibers, and talc powder separately to a moisture content of no more than 1%.

[0081] S2. Cellulose nanofibers were added to water to prepare a 1.5% (w / w) cellulose nanofiber dispersion. Nano-montmorillonite was then added, and the mixture was sheared and dispersed at 2000 rpm for 40 minutes at a pH of 5 and a temperature of 35°C. The resulting dispersion was spray-dried to obtain a layer-fiber composite barrier powder. This layer-fiber composite barrier powder was mixed with polylactic acid (PLA), PBAT, epoxidized soybean oil, a portion of carnauba wax, and a portion of antioxidant 1010 for the surface layer, and melt-blended in a twin-screw extruder. The temperatures of the twin-screw extruder zones were 150°C, 160°C, 167.5°C, and 170°C, respectively, and the screw speed was 175 rpm. After blending, the mixture was extruded, cooled, and pelletized to obtain the composite barrier masterbatch.

[0082] S3. Premix bamboo powder (without acidification and carnauba wax coating), thermoplastic starch, talc, and stearic acid. Then add polylactic acid, PBAT, epoxidized soybean oil, citric acid, remaining carnauba wax, and remaining antioxidant 1010 for the core layer to form the core layer mixture. Add the core layer mixture to a twin-screw extruder and melt-mix at 160°C, with a screw speed of 150 rpm and an average residence time of 2.5 minutes. After vacuum degassing and 115-mesh melt filtration, the mixture is extruded, cooled, and pelletized to obtain bamboo powder composite masterbatch. The vacuum degree in the vacuum degassing section is -0.0775 MPa.

[0083] S4. Add the composite barrier masterbatch to the first and second surface extruders respectively, and add the bamboo powder composite masterbatch to the core extruder. The heating temperatures of the first and second surface extruders from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively; the heating temperatures of the core extruder from the feed end to the discharge end are 150℃, 157.5℃, 162.5℃, and 167.5℃ respectively. The outlet temperature difference between the two surface melts is no greater than 3℃, and the outlet temperature difference between the surface melt and the core melt is no greater than 10℃. The screw speed of both surface extruders is 120 rpm, the screw speed of the core extruder is 100 rpm, and the melt pressure of each layer is 10 MPa.

[0084] S5. The first surface layer melt, core layer melt, and second surface layer melt are conveyed to the three-layer co-extrusion distributor and combined in the order of surface layer, core layer, and surface layer. The thickness ratio of the three layers is 15:70:15, and the thickness deviation between the two surface layers does not exceed 10% of the average thickness of the surface layer. The three-layer melt is extruded through a co-extrusion die at a temperature of 172.5℃ with a die gap of 0.9 mm.

[0085] S6. The three-layer co-extruded material is introduced between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. The three-layer material is subjected to a longitudinal stretch of 1.85 times, and the material is heat-set at 82.5°C for 55 seconds. Then, it is cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the composite packaging material of Comparative Example 2 is obtained.

[0086] Comparative Example 3: The difference between this comparative example and Example 2 is that, instead of preparing the surface barrier masterbatch and the core bamboo powder composite masterbatch separately, all components are mixed and then extruded into a single layer, without forming a three-layer structure of surface layer-core layer-surface layer, and without longitudinal stretching treatment.

[0087] The composite packaging material in this comparative example, by weight, comprises the following components: 57.5 parts polylactic acid, 25 parts PBAT, 20 parts bamboo powder, 11.5 parts thermoplastic starch, 5 parts nano-montmorillonite, 3.5 parts cellulose nanofibers, 3 parts carnauba wax, 3 parts epoxidized soybean oil, 1.15 parts citric acid, 3.5 parts talc, 0.9 parts stearic acid, and 0.45 parts antioxidant 1010.

[0088] The molding method of this comparative example includes the following steps: S1. Mix 115-mesh coarse bamboo powder and 300-mesh fine bamboo powder at a mass ratio of 1:2, and dry at 92.5℃ for 4 hours to ensure the bamboo powder moisture content is no higher than 2%. Mix the dried bamboo powder with a 4% (w / w) citric acid aqueous solution, heat-treat at 125℃ for 40 minutes, then add 57.5% (w / w) of carnauba wax, and mix and coat at 75℃. Dry thermoplastic starch to a moisture content no higher than 3%, and dry nano-montmorillonite, cellulose nanofibers, and talc powder separately to a moisture content no higher than 1%.

[0089] S2. Cellulose nanofibers were added to water to prepare a 1.5% (w / w) cellulose nanofiber dispersion. Nano-montmorillonite was then added, and the dispersion was sheared at 2000 rpm for 40 minutes at a pH of 5 and a temperature of 35°C. The resulting dispersion was then spray-dried to obtain a layered-fiber composite barrier powder.

[0090] S3. Premix the surface-treated bamboo powder, thermoplastic starch, sheet-fiber composite barrier powder, talc, and stearic acid. Then add all of the polylactic acid, PBAT, interface modifiers, remaining carnauba wax, and antioxidant 1010 to form a uniform mixture. Add the uniform mixture to a twin-screw extruder for melt mixing. The temperatures of the twin-screw extruder from the feed end to the discharge end are 150℃, 160℃, 167.5℃, and 172.5℃ respectively. The screw speed is 150 rpm, and the average residence time of the material is 2.5 minutes.

[0091] S4. The molten and mixed material is subjected to vacuum degassing and melt filtration. The vacuum degree of the vacuum degassing section is -0.0775 MPa, and the mesh size of the melt filter is 115 mesh. The filtered melt is extruded, cooled, and pelletized to obtain a homogeneous single-layer composite masterbatch.

[0092] S5. The single-layer composite masterbatch is added to a single-screw extruder. The heating temperatures of the single-screw extruder from the feed end to the discharge end are 155℃, 165℃, 172.5℃, and 177.5℃ respectively. The screw speed is 100 rpm, and the melt pressure is 10 MPa. The resulting melt is extruded through a single-layer sheet die at a temperature of 172.5℃, with a die gap of 0.9 mm, to form a single-layer composite sheet.

[0093] S6. The single-layer composite sheet is introduced into the space between cooling rollers at a temperature of 30°C for calendering and cooling. The linear speed of the cooling rollers is 8.5 m / min, and the calendering gap is 0.65 mm. No longitudinal stretching is applied to the single-layer composite sheet. The calendered material is heat-set at 82.5°C for 55 seconds, and then cooled to below 40°C at a cooling rate of 12.5°C / min. After edge trimming, traction, and winding, the single-layer composite packaging material of Comparative Example 3 is obtained.

[0094] The composite packaging materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to the tests shown in Table 1 below to verify the actual effect of the composite packaging materials.

[0095] Table 1

[0096] The packaging materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for appearance quality, thickness uniformity, oxygen permeability, water vapor permeability, tensile properties, interlaminar peel strength, puncture resistance, water absorption, barrier retention after hydrothermal treatment, thermal dimensional stability, biodegradability, and composting disintegration performance. A comprehensive evaluation can be made based on the differences in formulation and molding method among the various groups. Example 1 used the lower limit values ​​of each component, resulting in a higher proportion of resin phase, easier control of melt flow, and better surface integrity, tensile properties, and co-extrusion processing stability. Due to the relatively low addition of nano-clay, nano-cellulose, and plant wax, the improvement in barrier performance was relatively limited, but gas and water vapor permeation could still be reduced through the double-sided barrier surface layer and the hydrophobic treatment with bamboo powder. This example illustrates the feasibility of the present invention with lower amounts of barrier components, while also considering both processing performance and basic barrier performance.

[0097] Example 2 uses the median values ​​of each component, with a relatively balanced proportion among polylactic acid, biodegradable polyester, bamboo powder, thermoplastic starch, and the composite barrier component. Nanoclay and nanocellulose can form a layer-fiber composite barrier structure on both sides of the surface, while the treated coarse and fine bamboo powder can form a multi-level filling structure in the core layer. Epoxidized soybean oil and citric acid can improve the interfacial bonding between the hydrophilic filler and the resin matrix. Therefore, Example 2 can generally be considered as a preferred group for comprehensive performance, maintaining a good balance between oxygen barrier properties, water vapor barrier properties, interlayer bonding strength, puncture resistance, water absorption stability, and processing stability, making it suitable as a benchmark formulation for subsequent performance comparisons and industrial-scale trials.

[0098] Example 3 uses the upper limit of the value range for each component, where the contents of bamboo powder, thermoplastic starch, nano-clay, and nano-cellulose are all higher than in Examples 1 and 2. Higher contents of the lamellar and fibrous barrier components can increase the travel distance of gas molecules in the thickness direction of the material, and higher contents of plant wax can enhance the sealing effect on the water absorption channels of bamboo powder and the micropores of the material. Therefore, this example focuses on verifying the barrier effect under high filler content conditions. Due to the high content of solid components, the melt viscosity, dispersion uniformity, and tensile fracture properties of the material may be more easily affected. It is necessary to reduce filler agglomeration, bubbles, and interface defects by reducing the core layer mixing speed, strengthening vacuum degassing, and controlling the co-extrusion layer thickness ratio. If its appearance, interlayer bonding, and mechanical properties meet the judgment criteria, it can be shown that the upper limit formulation defined in this invention still has stable molding capability.

[0099] Comparative Example 1 did not include nano-clay and nanocellulose, therefore it could not form a tortuous permeation path composed of inorganic sheets and nanofibers on both sides of the surface. By comparing Comparative Example 1 with Example 2, the influence of the composite barrier powder on oxygen permeability, water vapor permeability, and barrier retention rate under humid and hot conditions can be determined. It is expected that the co-extruded layer structure and bamboo powder interface state of Comparative Example 1 will remain basically stable, but its gas barrier performance and water vapor barrier performance are lower than those of Example 2. This indicates that the improvement in barrier performance is not solely due to the three-layer structure, but is directly related to the synergistic dispersion structure of nano-clay sheets and nanocellulose.

[0100] Comparative Example 2 used the same component amounts as Example 2, but the bamboo powder was only dried; it was not surface-treated with citric acid, nor was a hydrophobic coating layer formed using plant waxes. By comparing Comparative Example 2 with Example 2, the effects of bamboo powder surface acidification and hydrophobic coating on water absorption, interlayer peel strength, tensile properties, and barrier retention after humid heat treatment can be evaluated. The untreated bamboo powder surface retains more hydrophilic hydroxyl groups and has weaker wettability with polylactic acid and biodegradable polyester, easily forming interfacial gaps around the bamboo powder. Therefore, Comparative Example 2 is expected to be weaker than Example 2 in terms of water absorption, interfacial bonding stability, and barrier retention under humid heat conditions. This can be used to demonstrate that bamboo powder pretreatment is not a routine drying step, but a necessary technical measure to maintain the long-term barrier stability of packaging materials.

[0101] Comparative Example 3 used the same raw material composition and bamboo powder pretreatment method as Example 2, but all components were uniformly mixed and then extruded in a single layer, without forming a three-layer structure of barrier surface layer—bamboo powder core layer—barrier surface layer, and without directional stretching. By comparing Comparative Example 3 with Example 2, the effects of component layering and co-extrusion directional structure on barrier performance, dimensional stability, and material uniformity can be evaluated. Single-layer mixing causes nano-clay, nano-cellulose, and bamboo powder to be randomly distributed throughout the material. The barrier components may be separated or adsorbed by the bamboo powder, making it difficult to form a continuous barrier region near the material surface. At the same time, the nano-clay sheets and bamboo powder without directional stretching are more dispersed in orientation and cannot fully form a multi-level barrier structure arranged along the material surface. Therefore, Comparative Example 3 is expected to be weaker than Example 2 in terms of oxygen permeability, water vapor permeability, thermal dimensional stability, and moisture and heat barrier retention, thus demonstrating the irreplaceable role of the three-layer co-extrusion structure and directional treatment.

[0102] A comprehensive comparison of the embodiments and comparative examples shows that the performance improvement of the present invention is not due to a simple increase in a single component, but rather stems from the synergistic effect of bamboo powder particle size distribution and hydrophobic treatment, composite dispersion of nano-clay and nano-cellulose, interface regulation of epoxidized soybean oil and citric acid, and the co-extrusion oriented structure of the surface layer-core layer-surface layer. Example 1 is used to demonstrate the feasibility of the lower limit of the formulation; Example 2 is used to demonstrate the comprehensive balance of mechanical properties, barrier properties, and processing properties; Example 3 is used to demonstrate the molding adaptability under conditions of higher bamboo powder and barrier filler content; Comparative Examples 1, 2, and 3 respectively verify the role of each key technical feature from three aspects: composite barrier component, bamboo powder surface treatment, and multilayer co-extrusion structure.

[0103] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A high-barrier bamboo powder biodegradable composite packaging material, characterized in that, By weight, it includes the following components: 45-70 parts polylactic acid, 15-35 parts biodegradable polyester, 10-30 parts bamboo powder, 5-18 parts thermoplastic starch, 2-8 parts nano clay, 1-6 parts nano cellulose, 1-5 parts plant wax, 1-5 parts epoxidized soybean oil, 0.3-2 parts citric acid, 1-6 parts talc, 0.3-1.5 parts stearic acid, and 0.1-0.8 parts antioxidant. The biodegradable polyester is poly(butylene adipate / terephthalate).

2. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The bamboo powder is composed of coarse bamboo powder and fine bamboo powder. The particle size of the coarse bamboo powder is 80-150 mesh, and the particle size of the fine bamboo powder is 200-400 mesh. The mass ratio of the coarse bamboo powder to the fine bamboo powder is 1:1 to 1:

3. The coarse bamboo powder is used to form a bamboo skeleton and limit material shrinkage, while the fine bamboo powder fills the gaps between the coarse bamboo powder, polylactic acid, and biodegradable polyester.

3. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The thermoplastic starch is obtained by plasticizing native starch, glycerol and water, wherein the mass ratio of native starch, glycerol and water is 100:20-35:8-18; The plasticizing process includes mixing native starch, glycerol and water, stirring at 70-95°C for 20-50 minutes, and then shearing plasticizing at 100-125°C to destroy the original crystalline structure of the native starch granules and form a continuous plasticized phase. The original starch is one or more of corn starch, tapioca starch or potato starch, and the moisture content of the resulting thermoplastic starch is 1% to 5%.

4. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The nano-clay is nano-montmorillonite, with a sheet thickness of 1-5 nanometers, a sheet transverse dimension of 80-500 nanometers, and a sheet aspect ratio of 30-200. The nano-montmorillonite is dispersed in the composite packaging material in the form of single layers and layer clusters consisting of 2 to 8 layers, with the spacing between adjacent layers in the layer cluster being 1.5 to 4 nanometers.

5. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The nanocellulose is cellulose nanofiber, which has a diameter of 5-30 nanometers, a length of 100-800 nanometers, an aspect ratio of 10-100, and a surface hydroxyl content of 5-12 mmol / g. A portion of the cellulose nanofibers is located between the nano-clay sheets, while another portion is distributed in the interface region between bamboo powder and polylactic acid, and between bamboo powder and biodegradable polyester.

6. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The epoxidized soybean oil and citric acid together form an interface regulating component, and the epoxy value of the epoxidized soybean oil is 5% to 8%. The preparation process of the interface-modifying component includes: heating epoxidized soybean oil to 70-100°C, adding citric acid and stirring for 10-30 minutes to uniformly disperse the citric acid in the epoxidized soybean oil, while retaining some unreacted epoxy and carboxyl groups.

7. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The plant wax is one or more of carnauba wax, rice bran wax, or beeswax, and its melting point is 60–90°C. The plant wax comprises a first portion of plant wax used to coat bamboo powder and a second portion of plant wax directly dispersed in a resin matrix formed from polylactic acid and biodegradable polyester. The mass ratio of the first portion of plant wax to the second portion of plant wax is 1:0.3 to 1:1.

5. The first portion of plant wax forms a coating layer with an average thickness of 0.1–2 micrometers on the surface of the bamboo powder, while the second portion of plant wax exists as a dispersed phase with a particle size not exceeding 5 micrometers within the continuous phase formed from polylactic acid and biodegradable polyester.

8. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The polylactic acid has a melt flow rate of 3-15 g / 10 min at 190°C and 2.16 kg load, and the biodegradable polyester has a melt flow rate of 2-10 g / 10 min under the same test conditions, with the difference between the two melt flow rates not exceeding 8 g / 10 min.

9. The high-barrier bamboo powder biodegradable composite packaging material according to claim 1, characterized in that, The nano-clay sheets in the composite packaging material are oriented along the surface of the packaging material, and the number of nano-clay sheets with an angle of no more than 30° between the sheet plane and the surface of the packaging material accounts for more than 60% of the total number of nano-clay sheets. The amount of bamboo powder with an angle of no more than 45° between its length direction and the surface of the packaging material accounts for more than 55% of the total amount of bamboo powder. The oriented structure is formed by extrusion casting, blown film stretching, or sheet calendering, so that the nano-clay sheets and bamboo powder are staggered in the thickness direction of the material.

10. A co-extrusion molding method for a high-barrier bamboo powder biodegradable composite packaging material, prepared based on the composite packaging material according to any one of claims 1-9, characterized in that, The specific steps include the following: S1. Weigh each component according to the formula, and dry and surface treat the bamboo powder, starch and filler; S2. Nano-clay and nano-cellulose are compositely dispersed to prepare a high-barrier masterbatch for surface layer. S3. Mix the treated bamboo powder, thermoplastic starch and matrix resin to obtain the core layer composite masterbatch. S4. Melt the surface masterbatch and core masterbatch separately, and control the melt temperature, pressure and flow state; S5. Combine the two surface melts with the core melt and co-extrude them to form a surface-core-surface structure. S6. Calender, stretch, cool and heat set the co-extruded material, and complete the trimming and winding.